Detection of corn adulteration in Brazilian coffee (Coffea arabica) by tocopherol profiling and Near-Infrared (NIR) spectroscopy - Winkler-Moser, Jill K.; Singh, Mukti; Rennick, Kathy A.; Bakota, Erica L.; Jham, Gulab; Liu, Sean X.; Vaughn, Steven F. (Journal of Agricultural and Food Chemistry, 2015)
Coffee is a high-value commodity that is a target for adulteration, leading to loss of quality and causing significant loss to consumers. Therefore, there is significant interest in developing methods for detecting coffee adulteration and improving the sensitivity and accuracy of these methods. Corn and other lower value crops are potential adulterants, along with sticks and coffee husks. Fourteen pure Brazilian roasted, ground coffee bean samples were adulterated with 1–20% of roasted, ground corn and were analyzed for their tocopherol content and profile by HPLC. They were also analyzed by near-infrared (NIR) spectroscopy. Both proposed methods of detection of corn adulteration displayed a sensitivity of around 5%, thus representing simple and fast analytical methods for detecting adulteration at likely levels of contamination. Further studies should be conducted to verify the results with a much larger sample size and additional types of adulterants.
Keywords: Adulteration; Coffea arabica; Coffee; Near-infrared spectroscopy; Tocopherol